DETECTION FINANCIAL STATEMENT FRAUD SHARIAH BANK IN INDONESIA: ROLE OF POLITIC CONNECTION, FINANCIAL STABILITY, IN EFECTIVE MONITORING - Arinta, Yusvita Nena; Rahman, Taufikur; Khilmiyah, Ismi (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
Financial statement fraud is an effort to achieve the goal, namely to gain profits by committing fraudulent practices, harming other parties either intentionally or negligently. Companies are often oriented towards the appearance of good financial performance, with the aim of pleasing all stakeholders in the selection of financial statements. This causes the management as an agent to do everything in the process of preparing financial statements. Agents try to show that the company's financial statements are able to penetrate and win in the stock market The research method used in this study is a quantitative method with the aim of measuring the strength of the relationship between dependent variables and independent variables. The determination of the sample carried out is purposive, that is, it is selected with certain considerations and objectives. The sample used is a bank with a sharia base in Indonesia that has met the criteria for research needs. There are 12 Islamic banking companies during the 2019-2023 period that will be studied in this study. political connections have no effect on financial statement fraud. financial stability has an effect on financial statement fraud. that innefective monitoring has no effect on financial statement fraud. Compared to fraudulent financial statements The limitation of this research is that the variables used to detect fraud are not comprehensive enough, so recommendations for future research could reveal variables that can detect financial statement fraud. The second limitation is that the data used is only data from Islamic banks in Indonesia. Future research can include data comprehensively across countries so that research results can be generalized.